Influence of abutment design on retention of metal copings cemented to implants - da Cunha Jr, Albano Porto (Acta Biomater Odontol Scand, 2016)
Objective The study evaluated the influence of abutment design on the retention of implant-cemented metal copings. Material and methods Two abutments of the same system with the same indications, height and the total occlusal convergence, but of different designs were evaluated. Ten RN synOcta abutments (Straumann, Waltham, MA) and ten RN titanium solid abutments (Straumann, Waltham, MA) were tightened to 35 Ncm on 20 implant analogs previously placed in resin blocks. Twenty plastic burnout copings were waxed, included, cast and machined by a single operator. Coping was inspected for surface irregularities using a stereomicroscope at 10x magnification, and then, they were cemented (Temp Bond NE, Kerr, Romulus, MI) with 5 kg load for 10 min. The samples were stored for 24 h in room temperature and 100% humidity and then subjected to pull-out test at a crosshead speed of 0.5 mm/min. The load required to dislodge each coping was recorded (kgf) and and mean values for each group statistically calculated. Means and standard deviations of loads at failure were analyzed using Student’s t-test. Results The mean load required to dislodge the copings showed by synOcta abutments (11.19 kgf) was statiscally higher than s solid abutments (10.18 kgf). Conclusions: It was concluded that the abutment design influenced significantly the retention of metal copings.